int a[maxn][maxn][maxn];

int sum(int x1, int y1, int z1, int x2, int y2, int z2) {
    return a[x2][y2][z2] - a[x1 - 1][y2][z2] - a[x2][y1 - 1][z2] -
           a[x2][y2][z1 - 1] + a[x1 - 1][y1 - 1][z2] + a[x1 - 1][y2][z1 - 1] +
           a[x2][y1 - 1][z1 - 1] - a[x1 - 1][y1 - 1][z1 - 1];
}

void init(int n) {
    for (int i = 0; i < n; i++)
        for (int k = 0; k < n; k++)
            for (int t = 0; t < n; t++) a[i][k][t] += a[i - 1][k][t];
    for (int i = 0; i < n; i++)
        for (int k = 0; k < n; k++)
            for (int t = 0; t < n; t++) a[i][k][t] += a[i][k - 1][t];
    for (int i = 0; i < n; i++)
        for (int k = 0; k < n; k++)
            for (int t = 0; t < n; t++) a[i][k][t] += a[i][k][t - 1];
}
最后修改:2020 年 07 月 30 日 10 : 17 PM